2021
DOI: 10.1029/2020jb021541
|View full text |Cite
|
Sign up to set email alerts
|

A Consistently High‐Latitude South China From 820 to 780 Ma: Implications for Exclusion From Rodinia and the Feasibility of Large‐Scale True Polar Wander

Abstract: Earth's lithosphere moves through two fundamental mechanisms. The more familiar of these mechanisms are tectonic motions-that is, differential movement between lithospheric plates. The second mechanism is the rotation of the entire silicate Earth in order to maintain rotational equilibrium. On any rotating planetary body, changes in the distribution of mass on (e.g., the melting of ice sheets;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 116 publications
(271 reference statements)
3
42
0
Order By: Relevance
“…But the poles from the Liantuo Formation reveal significantly lower latitudes (Evans et al, 2000;Jing et al, 2015Jing et al, , 2021. Park et al (2021) reported a precise zircon U-Pb age at 779.52 ± 0.26 Ma, through the use of the CA-ID-TIMS (chemical abrasion isotope dilution thermal ionization mass spectrometry) method, from a tuff bed ∼15 m below the paleomagnetic sampling horizon of the upper Liantuo Formation in Evans et al (2000). If the dating results do represent the stratum age rather than detrital materials, the age of the lower Liantuo Formation should be older than ca.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But the poles from the Liantuo Formation reveal significantly lower latitudes (Evans et al, 2000;Jing et al, 2015Jing et al, , 2021. Park et al (2021) reported a precise zircon U-Pb age at 779.52 ± 0.26 Ma, through the use of the CA-ID-TIMS (chemical abrasion isotope dilution thermal ionization mass spectrometry) method, from a tuff bed ∼15 m below the paleomagnetic sampling horizon of the upper Liantuo Formation in Evans et al (2000). If the dating results do represent the stratum age rather than detrital materials, the age of the lower Liantuo Formation should be older than ca.…”
Section: Discussionmentioning
confidence: 99%
“…Reported ca. 824‐800 Ma paleomagnetic data (Jing et al., 2020; Li et al., 2004; Niu et al., 2016; Park et al., 2021; Xian et al., 2020) and the ca. 770 Ma pole all indicate a high latitudinal position for the SCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reconstruction of North China to Laurentia follows Ding et al (2021). The omission of South China from Rodinia follows Park et al (2021b). The reconstruction implements Kalahari and Amazonia cratons as conjugates with Laurentia in the Grenvillian orogeny (Hoffman, 1991).…”
Section: Mirovoi Oceanmentioning
confidence: 99%